Ewolucja ustawodawstwa i orzecznictwa Sądu Konstytucyjnego Ukrainy w kwestii języka państwowego - Rafał Czachor (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The language issue was among the most salient problems of Ukrainian public life since gaining independence in 1991. There is no doubt that it was one of the crucial factors that influenced Ukrainian politics and driving its dynamics. National parties have advocated for declaring the Ukrainian language as the sole official language and in doing so eliminating the Russian language from the public space. The Communists and parties personally and financially related to pro-Russian parties have tended to value the Russian language to preserve bilingualism and even maintain its factual dominance in everyday life.